Surgical Outcome of Traumatic Cataract Following Corneal Perforation in Children in a Tertiary Eye Care Centre in Nepal - Shrestha, Ujjowala Devi; Adhikari, Srijana (Journal of Nepal Paediatric Society, 2016)
Introduction: Traumatic paediatric cataract is challenging and its management is difficult. It is associated with other distortion of ocular anatomy and subsequent post- operative complication poses more problems. It is mostly unilateral. The purpose of this study is to assess the outcome of traumatic cataract following corneal perforation in Nepalese children in a tertiary eye hospital in Nepal. Material and Methods: It was a retrospective review of medical records of children who developed cataract following perforating corneal injuries. The study included 69 cases diagnosed as unilateral traumatic cataract over a period of 70 months (January 2010 till October 2015) at Tilganga Institute of Ophthalmology (TIO). Traumatic cataracts caused by other than the perforating corneal injuries were excluded from the study. Results: Children between 6 to 10 years of age had highest percentage of ocular trauma. Boys were more commonly affected than girls. Forty two percentages of children had visual outcome of better than or equal to 6/18.Poor visual outcome was mainly due to anterior segment pathology- corneal scar (14.49%).Posterior segment pathology like macular scar, vitreous haemorrhage and retinal detachment contributed to 7.34% of the cause. Conclusion: Outcome of the traumatic cataract surgery varied. Visual outcome of post traumatic cataract after corneal perforation was dependent on multiple factors like co- existence of the anterior and posterior segment trauma, per –operative and post-operative challenges. Prompt and good management of traumatic cataract can result in good visual outcome. J Nepal Paediatr Soc 2016;36(1):50-55